PENGARUH BOARDGAME ‘GERMAS GAME’ DAN METODE CERAMAH TERHADAP PENGETAHUAN DAN SIKAP GERAKAN MASYARAKAT HIDUP SEHAT PADA REMAJA PEREMPUAN (STUDI PADA SISWI KELAS 8 SMPIT DAARUSSALAAM, SANGATTA, KALIMANTAN TIMUR) - Bilqis Nabila; Syamsulhuda Budi Mustofa; Bagoes Widjanarko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
The adolescent age group has risky behaviors that have a negative impact on health in the coming decades, such as non-communicable diseases. Risk prevention programs with an understanding referring to adolescents can help adolescents increase awareness of healthy behaviors and behavior changes for adolescents with the early non-communicable disease phase. The Indonesian Ministry of Health specifically reminds the public to maintain health through the Healthy Living Community Movement (GERMAS) in order to create a healthy Indonesia and prevent non communicable diseases. This study uses the Germas Game boardgame and lecture method to provide comprehensive health information. The subjects of this study were 40 students of 8th grade of Daarussalaam Middle School, Sangatta, East Kalimantan. The control group was given intervention through the lecture method only. The experimental group received the Germas Game board game as a complement to the intervention. The results showed a significant difference in knowledge between control group and experimental group (mean=6.05;p=0,000). The data showed that the increase in knowledge in the experimental group (mean=14,45) was greater than the increase in knowledge in the control group (mean=8,4). The results also showed significant differences in attitudes between the control and experimental groups (mean=4,35;p=0,000). It can be concluded that intervention by lecturing and playing the Germas Game board game is more effective in increasing knowledge and attitudes in adolescents.